The palgrave handbook of literary translation - Boase-Beier, Jean; Fisher, Lina; Furukawa, Hiroko (Palgrave Studies in Translating and Interpreting, 2018)
This Handbook offers a comprehensive and engaging overview of contemporary issues in Literary Translation research through in-depth investigations of actual case studies of particular works, authors or translators. Leading researchers from across the globe discuss best practice, problems, and possibilities in the translation of poetry, novels, memoir and theatre. Divided into three sections, these illuminating analyses also address broad themes including translation style, the author-translator-reader relationship, and relationships between national identity and literary translation. The case studies are drawn from languages and language varieties, such as Catalan, Chinese, Dutch, English, French, German, Hebrew, Italian, Japanese, Nigerian English, Russian, Spanish, Scottish English and Turkish. The editors provide thorough introductory and concluding chapters, which highlight the value of case study research, and explore in detail the importance of the theory-practice link. Covering a wide range of topics, perspectives, methods, languages and geographies, this handbook will provide a valuable resource for researchers not only in Translation Studies, but also in the related fields of Linguistics, Languages and Cultural Studies, Stylistics, Comparative Literature or Literary Studies